Alloying aluminum with Fe using laser induced plasma technique - Alwafi, Y. A. (2012)
A new surface modification technique is demonstrated using laser induced plasma (LIP) to increase the hardness of the surface layer. This LIP treatment provides a very high heating and fast cooling mechanism that can be used to form alloyed layer on a material surface. The hardness of the alloyed material is measured and the results show that the alloyed surface is 3 times as hard as the untreated surface and a single Fe alloyed aluminum surface is harder than the one formed by the mixture of Fe and Cu. The micro-hardness of the alloy increases with the number of pulses at a rate of around 4 HV/pulse. The maximum hardness of 93.0 HV is obtained with the use of single Fe after exposure to 7 pulses of the laser.